PERUBAHAN FUNGSI DAN BENTUK SENI PAHAT, SENI PATUNG SUKU ASMAT DI PAPUA SEBAGAI PRODUK KERAJINAN - Diah Asmarandani (Universitas Trisakti, 2007)
AbstractAs tradition art, artistic of people sculpture and statue Asmat earn grouped in primitive culture/artefact - primitive art, this thing is because ofform of physical from material culture function and material culture is more majored, and also forming process is not addressed for aesthetic function; in the growth primitive art from people Asmat become appearance idea primitivism in the world of art. Art, craft and design masterpiece with theme primitive art/primitive culture from people Asmat many produced in so many forms like: furniture, mural, paintings and households appliances as effort so that culture of people materials Asmat don't become extinct. Form of to many becoming new inspiration in the craft world, become attention of primitive art observer and consumer, and also producer/craft industrial.Keywords: primitive artefact/culture, primitivism, Asmat craft.AbstrakSebagai seni tradisi, seni patung dan seni pahat orang Asmat dapatdikelompokan kedalam primitive culture/artefact primitive art, hal inidisebabkan oleh bentuk fisik dari budaya material dan fungsi budaya material lebih diutamakan, serta proses pembentukan tidak ditujukan untuk fungsi estetis; dalam perkembangannya primitive art dari orang Asmat menjadi ide munculnya primitivism dalam dunia seni. Karya seni, karya kerajinan dan karya desain dengan tema primitive art/primitive culture dari orang Asmat banyak diproduksi dalam berbagai bentuk seperti: furnitur, mural, alat-alat rumah tangga dan lukisan-lukisan kulit pohon sebagai usaha agar